Sacral Sound-Engineering - BUDZYNSKI, Gustaw (Archives of Acoustics, 2011)
Organologic and campanologic acoustical problems due to applications to sacralobjects are characterized on ground of numerous reviewed publications and engineeringreports. Participation of several involved research centres, mostly Polish, atsolving these problems is evaluated. Some desirable future developments are indicated.Appendices bring examples of documentation on selected investigated objects.